The Influence of Quality Work Life Factors on Job Satisfaction and Its Implication on Employees Performance at Dinda Jatiuwung Tangerang Hospital - Astri Arri Febrianti (universitas Pamulang, 2022)
This research aims to find out the partial and simultaneous influence of career development, occupational safety and health, compensation for job satisfaction at Dinda Jatiuwung Tangerang Hospital, to find out the partial influence between job satisfaction variables on employee performance at Dinda Jatiuwung Tangerang Hospital. The method used in this study uses multiple linear regression analysis and simple linear regression, the population in this study is an employee at Dinda Hospital, Tangerang as many as 359 employees, the sample will be calculated using the slovin formula. So the sample in this study is employees at Dinda Hospital, Tangerang as many as 189 employees who will be used as respondents to fill out questionnaires. The results stated that career development variables affect job satisfaction. Occupational safety and health variables affect job satisfaction. Compensation variables affect job satisfaction. Variables of career development, occupational safety and health, compensation have a simultaneous effect on job satisfaction. Job satisfaction variables affect employee performance.